Forming short period sub-stellar companions in 47 Tucanae - II: analytical expressions for the orbital evolution of planets in dense environments - Winter, Andrew J.; Clarke, Cathie J; Rosotti, Giovanni; Giersz, Mirek (Monthly notices of the Royal Astronomical Society, 2022)
Short period, massive planets, known as hot Jupiters (HJs), have been discovered around ∼1 per cent of local field stars. The inward migration necessary to produce HJs may be ‘low eccentricity’, due to torques in the primordial disc, or ‘high eccentricity’ (HEM). The latter involves exciting high orbital eccentricity, allowing sufficiently close passages with the host star to raise circularizing tides in the planet. We present an analytical framework for quantifying the role of dynamical encounters in high density environments during HEM. We show that encounters can enhance or suppress HEM, depending on the local stellar density and the initial semimajor axis a0. For moderate densities, external perturbations can excite large eccentricities that allow a planet to circularize over the stellar lifetime. At extremely high densities, these perturbations can instead result in tidal disruption of the planet, thus yielding no HJ. This may explain the apparent excess of HJs in M67 compared with their local field star abundance versus their apparent deficit in 47 Tuc. Applying our analytical framework, we demonstrate that for an initial massive planet population similar to the field, the expected HJ occurrence rate in 47 Tuc is fHJ = 2.2 × 10−3, which remains consistent with present constraints. Future large (sample sizes ≳105) or sensitive transit surveys of stars in globular clusters are required to refute the hypothesis that the initial planet population is similar to the solar neighbourhood average. Non-detection in such surveys would have broad consequences for planet formation theory, implying planet formation rates in globular clusters must be suppressed across a wide range of a0.